ANALISA PRODUK LAYANAN IGD DENTAL DI RSGM YARSI BERDASARKAN STP (SEGMENTING, TARGETING, POSITIONING): ANALISA PRODUK LAYANAN IGD DENTAL DI RSGM YARSI BERDASARKAN STP (SEGMENTING, TARGETING, POSITIONING) - Ni Putu Retno Ariani (Yayasan Pendidikan Medika Indonesia, 2021)
Dental emergency installation (IGD Dental) is a healthcare service that handles serious teeth, jaw and gum problems that need immediate care to prevent permanent damage. This research aims to describe IGD Dental service at Yarsi Dental Hospital (RSGM Yarsi), Central Jakarta, based on segmenting, targeting and positioning. The research used descriptive research method with quantitative approach. The research’s data was gathered through secondary data with inclusion criteria that consisted of complete data on new patients who visited IGD Dental from September to November 2020, resulting in 133 samples. The result showed that in market segmentation, most of new patients who visited IGD Dental were male (71 people or 53.40%) in the productive age group between 18 to 40 years old (118 people or 88.72%) with education levels of undergraduate and post-graduate (82 people or 61.65%). In regards of their jobs, majority of them worked as employees (34 people or 35.09%) and lived in Jakarta (116 people or 87.21%). Their frequent payment methods were cash, credit cash (tunai kredit) and credit cards (111 people or 83.45%). The research’s determined target market was based on market segmentations. Regarding the research’s positioning, Yarsi Dental Hospital highlights 24-hour IGD Dental. The research concluded that Yarsi Dental Hospital had done target segmentation analysis by targeting several segmentations which later could be used for marketing and determining the hospital’s strategy. Keywords: IGD Dental; segmenting; targeting; positioning.